2016
DOI: 10.21077/ijf.2016.63.4.52912-02
|View full text |Cite
|
Sign up to set email alerts
|

GIS based mapping of spatio-temporal distribution pattern of ribbonfish Trichiurus lepturus (Linnaeus, 1758) along Saurashtra coast, India

Abstract: Identification of spatio-temporal distribution of fish species represents fundamental information for stock assessment which in turn is essential for formulation of fishery management plans as well as for GIS based decision making. This study investigated the spatio-temporal distribution and abundance of different life stages of ribbonfish, Trichiurus lepturus (Linnaeus, 1758) off Saurashtra coast. Geographical coordinates of fishing and allied information on the time of fishing, depth of the fishing area as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, a low number of individuals were observed during this period. This pattern has been observed for this species in various regions worldwide and is likely attributed to their migratory behavior for reproduction, which leads them toward deeper waters (James, 1960;Martins & Haimovici, 1997;Magro, 2006;Abdul Azeez et al, 2016). For instance, in the northern Gulf of Mexico, the significant occurrence of planktonic postlarvae in deep tows (at depths of 20-37 m) and their absence in surface tows, along with the absence of adult individuals in coastal areas during late fall and early winter, are considered indicative of winter spawning occurring at depths greater than 37 m (Dawson, 1967).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, a low number of individuals were observed during this period. This pattern has been observed for this species in various regions worldwide and is likely attributed to their migratory behavior for reproduction, which leads them toward deeper waters (James, 1960;Martins & Haimovici, 1997;Magro, 2006;Abdul Azeez et al, 2016). For instance, in the northern Gulf of Mexico, the significant occurrence of planktonic postlarvae in deep tows (at depths of 20-37 m) and their absence in surface tows, along with the absence of adult individuals in coastal areas during late fall and early winter, are considered indicative of winter spawning occurring at depths greater than 37 m (Dawson, 1967).…”
Section: Discussionsupporting
confidence: 57%
“…. Similarly, in the northeastern Arabian Sea, this species can be found at depths ranging from 10 to 200 m (AbdulAzeez et al, 2016). These studies have demonstrated correlations between depth and abundance, as well as shifts in length frequency in correspondence with different climate seasons.…”
mentioning
confidence: 88%
“…GeoMedia Professional 2014 and its extensions were used to create georeferenced maps for the abundance and disribution of Thunnus tonggol. The data collected were entered in an MS excel 1997-2003 format compatible to GeoMedia Professional 2014 GIS platform as followed by Azeez et al (2016). Coastline and bathymetry maps were digitised from available nuatical maps and saved in shapefile format (.shp).…”
Section: Methodsmentioning
confidence: 99%
“…In India, the application of GIS in marine fisheries has been considerably slower but much awareness has developed recently and formed one of the major topics of research during the last decade. ICAR-CMFRI also attempted and demonstrated the utility of GIS in marine fishery resource mapping (Dineshbabu et al, 2012b;Abdul-Azeez et al, 2016).…”
Section: Temporal Mappingmentioning
confidence: 99%